1994
DOI: 10.1200/jco.1994.12.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of interferon gamma to potentiate cyclosporine-induced graft-versus-host disease in women undergoing autologous bone marrow transplantation for breast cancer.

Abstract: CSA-induced GVHD can be safely augmented by IFN-gamma in women treated with high-dose alkylating agents and autologous bone marrow transplantation. There is little evidence of increased toxicity. Evidence of antitumor efficacy awaits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 16 publications
0
46
1
Order By: Relevance
“…12 It has been demonstrated that CsA-induced GVHD can be augmented by interferon-␥. 34 Ratanatharathorn et al 35 reported that interferon-␣ administration can both induce autologous GVHD and enhance autologous GVHD induced by CsA. In addition, interleukin-2 amplifies antitumor activity and shows synergism with CsA in induction of a potent graftversus-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been demonstrated that CsA-induced GVHD can be augmented by interferon-␥. 34 Ratanatharathorn et al 35 reported that interferon-␣ administration can both induce autologous GVHD and enhance autologous GVHD induced by CsA. In addition, interleukin-2 amplifies antitumor activity and shows synergism with CsA in induction of a potent graftversus-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and II studies were performed to evaluate the potential efficacy of post transplant immune modulation using CsA with or without IFN-g to induce auto-GVHD. 10,14,[21][22][23][24][25][26] We will review these data from a clinical and mechanistic perspective and speculate as to how auto-GVHD might be more effectively harnessed in future clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclosporin A-induced syngeneic and autologous GVHD has been observed experimentally in rodents [15][16][17] and clinically in cancer patients. [18][19][20][21][22][23] The data presented in this report demonstrate that a GVT mechanism is present in mice with SGVHD. Mice in which SGVHD was induced rejected a minimal tumor challenge of a class II Ϫ B cell lymphoma after cessation of CsA therapy and the rejection coincided with histological evidence of the disease.…”
Section: Discussionmentioning
confidence: 90%
“…[15][16][17] Although the mechanism(s) by which CsA treatment of syngeneic reconstituted animals induces syngeneic GVHD (SGVHD) is not totally understood, CsA-induced autologous GVHD has been used in cancer patients post-transplant to assess the antitumor effects. [18][19][20][21][22][23][24] A low-grade cutaneous GVHD which spontaneously regressed was induced in a high percentage of the patients following autologous transplantation and CsA treatment. Isolated T cells from such patients showed the ability to lyse autologous peripheral blood lymphocytes in vitro.…”
mentioning
confidence: 99%